Legal Politics of Regional Head Offices for The 2019-2024 Period After The Constitutional Court Decision Based on Constitutional Theory - Indra Lorenly Nainggolan (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Article 201 paragraph 5 of Law Number 10 of 2016 has limited the term of office of regional heads and deputy regional heads who are appointed for the 2019 – 2023 term of office. Article 3 of Law Number 10 of 2016 confirms that elections are held every 5 (five) years. The term of office of regional heads and deputy regional heads is 5 years. The provisions of Article 201 deny this and violate the provisions of Article 18 paragraph 4 and Article 28D paragraph 1 of the 1945 NRI Constitution. This research uses normative juridical and uses conceptual, case and statutory approaches. The Constitutional Court's argument is that every position of regional head and deputy regional head is mandatory for 5 (five) years. Anything less is a violation of the constitution and democracy. The majority principle in democratic principles guarantees the sovereignty of the people running with the rule of law in the constitution, especially the protection of human rights. The voice of the majority of the people must not be co-opted with the political and legal policies of law makers in the name of the people. The transitional legal politics of the policy of simultaneously filling the positions of regional head and deputy regional head must be improved in the space of democracy and the rule of law. The principle of guaranteeing freedom and equal treatment before the law in Article 28D paragraph 1 of the 1945 Constitution of the Republic of Indonesia, emphasizes that state power must be exercised in a way that does not violate the constitution.